Conditioned pain modulation and pain sensitivity in functional somatic disorders: The DanFunD study. (10th August 2021) - Petersen, Marie Weinreich; Skovbjerg, Sine; Jensen, Jens Søndergaard; Wisbech Carstensen, Tina Birgitte; Dantoft, Thomas Meinertz; Fink, Per; Benros, Michael Eriksen; Mortensen, Erik Lykke; Jørgensen, Torben; Gormsen, Lise Kirstine
Abstract: Background: Disrupted pain regulation has been proposed as a component in functional somatic disorders (FSD). The objective of this study was to examine a general population sample, encompassing three delimitations of FSD while assessing pain sensitivity and conditioning pain modulation (CPM). Methods: Pressure pain thresholds (PPTs) at the tibialis and trapezius muscles were recorded at baseline. During cold pressor stimulation of the hand, the tibialis PPTs were re‐assessed and the difference from baseline measures defined the CPM effect. Participants ( n = 2, 198, 53% females) were randomly selected from the adult Danish population. FSD was established by self‐reported symptom questionnaires. Results: With a few exceptions, only weak associations were seen between PPTs and CPM in cases with FSD ( p > .1). A high PPT was associated with lower odds of having multi‐organ bodily distress syndrome (OR PPT trapezius : 0.66, 95% CI: 0.49–0.88, p = .005), with the symptom profile characterized by all symptoms (OR PPT trapezius : 0.72, 95% CI: 0.58–0.90, p = .003 and OR PPT tibialis : 0.75, 95% CI: 0.62–0.91, p = .004), and with multiple chemical sensitivity (OR PPT trapezius : 0.81, 95% CI: 0.67–0.97, p = .022). High CPM was associated with high odds of having irritable bowel (OR CPM relative : 1.22, 95% CI: 1.04–1.43, p = .013 and OR CPM absolute = 2.66, 95% CI: 1.07–6.45, p = .033). Conclusion: However, only PPT measured over the trapezius muscle were still significant after correction for multiple testing for the symptom profile characterized by all symptoms. Findings from this study do not support altered pain regulation in questionnaire‐based FSD which is in contrast with the existing presumption. Further epidemiological studies in this field are needed. Significance: Disrupted pain regulation as measured by abnormal pain thresholds has been hypothesized as a central mechanism in Functional Somatic Disorders (FSD). The hypothesis has been raised in clinical setting where patients presented subjective and objective features of hypersensitivity. The present population‐based study does not support this notion. This points to the importance of further studies into the underlying pathophysiology mechanisms of FSD.